Implementing security for internet of things (IoT) - Low, Jian Hui (2017)
Internet of Things (IoT) is a network of physical devices connected, thus allowing those devices to communicate with one another. It has become a common buzzword in today culture and will become the next technology that shapes the future. [1] As more devices transform into IoT devices, it raises a concern regarding the security and privacy of that information to send by those devices. [2] This report suggests the use of modern day encryption algorithm and implementing it into IoT devices to secure the information.